2022
DOI: 10.3390/foods11121732
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Perception of Beef Quality and How to Control, Improve and Predict It? Focus on Eating Quality

Abstract: Quality refers to the characteristics of products that meet the demands and expectations of the end users. Beef quality is a convergence between product characteristics on one hand and consumers’ experiences and demands on the other. This paper reviews the formation of consumer beef quality perception, the main factors determining beef sensory quality, and how to measure and predict beef eating quality at scientific and industrial levels. Beef quality is of paramount importance to consumers since consumer perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 170 publications
1
18
0
1
Order By: Relevance
“…Meat tenderness depends on several factors, including background toughness related to connective tissue, the degree of muscle contraction, muscle myofibril degradation by proteolysis during aging, i.m. adipose tissue content, and protein denaturation during cooking [30][31][32]. The Warner-Bratzler shear force is an instrumentally measured value of tenderness.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
See 2 more Smart Citations
“…Meat tenderness depends on several factors, including background toughness related to connective tissue, the degree of muscle contraction, muscle myofibril degradation by proteolysis during aging, i.m. adipose tissue content, and protein denaturation during cooking [30][31][32]. The Warner-Bratzler shear force is an instrumentally measured value of tenderness.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…Meat flavor is a complex sensation that involves a combination of olfactory, gustatory, and trigeminal sensations that detect basic taste and aroma [ 33 ]. Meat juiciness is characterized by the perceived amount of juice and the level of lubrication during mastication of the meat in the mouth [ 30 ].…”
Section: Factors Affecting Beef Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…The sensorial properties may or not change, according to the purpose, for example, it has been shown that nanoemulsion does not change the appearance of the food when added, but in other cases, it can be used for delivery of lipophilic ingredients such as flavor components, then they can mask unpleasant tastes and odors, as in fish oils. They can also help reduce calories by increasing the water and/or air content as in nanoemulsions, such as ice cream, reducing sugar and oil content by decreasing the size of air bubbles, and thus increasing creaminess [ 16 ]. For example, the use of nanoemulsions with Zataria multiflora and cinnamaldehyde essential oils for the preservation of ground beef patties cooked in a microwave showed better sensorial properties, improving this characteristic [ 17 ].…”
Section: Effects Of Nanosystems On Sensory Properties Of Foodmentioning
confidence: 99%
“…Recently, consumers prefer tender meat to fatty meat. Among various meat traits, tenderness and texture of cattle are among the most important factors affecting the quality evaluation of consumers [3][4][5].…”
Section: Introductionmentioning
confidence: 99%